Lebih Baik Sekolah Daripada Main: Studi Tentang Masyarakat Pendukung Mts Al Muhajirin Bantargebang Bekasi, Jawa Barat - Wahid Khozin (Badan Litbang dan Diklat Kementerian Agama RI, 2022)
Abstract This research discusses community support for madrasah tsanawiyah (MTs) Al Muhajirin located in the place of final disposal garbage Bantargebang. The community who live around MTs are scavengers whose life is collecting garbage at the Bantargebang TPA. The environment of the madrasa tends to be exploitative and sometimes ignores the norm. The community view of education is straightforward,